2014
DOI: 10.1002/sys.21294
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Complex System through Different Lenses: Impact of Decomposition Perspective on System Architecture Analysis

Abstract: Creating a representation of the base system architecture is one of the first and most critical steps for system development. Typically, the system architect would start by decomposing the existing or proposed system into smaller subsystems or modules. It is widely recognized that at the overall systems level a system can be viewed from different viewpoints. However, unlike often assumed, also when focusing on a single view, such as a systems view, the system decomposition can be done in many alternative ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
(42 reference statements)
0
27
0
Order By: Relevance
“…As noted in the previous sections, the results of this methodology depend strongly on the input functional Past work has illustrated significant impact of the decomposition style and degree of decomposition on the architectural representation [23]; correspondingly, it is clear that different modules would be generated by this methodology given different degrees of granularity of the input functions. Finally, we intend to further extend this work by characterizing the links made between functions to create modules, allowing for an evaluation of module or vehicle complexity and flexibility as in [24] or [25].…”
Section: Discussionmentioning
confidence: 98%
“…As noted in the previous sections, the results of this methodology depend strongly on the input functional Past work has illustrated significant impact of the decomposition style and degree of decomposition on the architectural representation [23]; correspondingly, it is clear that different modules would be generated by this methodology given different degrees of granularity of the input functions. Finally, we intend to further extend this work by characterizing the links made between functions to create modules, allowing for an evaluation of module or vehicle complexity and flexibility as in [24] or [25].…”
Section: Discussionmentioning
confidence: 98%
“…However, owing to the different preferences of various stakeholders and system design constraints, it is often extremely difficult to generate a system decomposition configuration that satisfies all the needs from stakeholders and the imposed constraints. In fact, it has been quantitatively demonstrated that the perspectives of stakeholders of the system can significantly change the final decomposition of the system …”
Section: Literature Reviewmentioning
confidence: 99%
“…The Department of Defense Architectural Framework (DoDAF) addresses this issue for weapons systems wherein the system architecture has been organized from systems, operational, and technical viewpoints . This idea was generalized and refined as three unique architectural decomposition perspectives: function, assembly, and maintenance‐based decompositions . The initial decomposition process is executed by designers and system architects on a functional basis, and the decomposition is extended to increase the level of granularity of the decompositions .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The initial decomposition process is executed by designers and system architects on a functional basis, and the decomposition is extended to increase the level of granularity of the decompositions . However, in complex systems, decomposing a product into its atomic constituents is highly impractical . To this end, the granularity of the system decomposition should be fine enough to differentiate viewpoints of various perspectives (e.g., assembly and maintenance), yet not too fine to be impractical .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation